O mercado e o sonho: Lê e Miguilim duas propostas de editoração do livro infantil e juvenil - Maria da Conceicao Carvalho (1993)
The study recovers, through a case study, the recent history of literature book publishing in Minas Gerais, Brazil, for children and young people in the context of the literature boom for this age group, with beginnings in the l970's. It analyses the evolution of the two publishing houses Lé and Miguilim in the line of literature for children and young people through 1982- 91. To make it efective this study was based on the literature, on the recollections of the subjects about the historical facts and on institucional documentation. The results suggest that the structure of these publishing houses on the literature book for children and young people represents a rupture in the hegemony of Rio de Janeiro and São Paulo in the Brazilian editorial field. These publishing houses represent opposite tendencies in the Minas Gerais editorial field: the commercial and cultural tendencies. The present crisis in Brazilian society has greatly affected the structure ofthe editorial field indicating the dominance of the commercial tendency.